Comparing Quality of Dying and Death Perceived by Family Members and Nurses for Patients Dying in US and Dutch ICUs - Gerritsen, Rik T; Koopmans, Matty; Hofhuis, José G M; Curtis, J Randall; Jensen, Hanne Irene; Zijlstra, Jan G; Engelberg, Ruth A; Spronk, Peter E (Chest, 2017)
The Quality of Dying and Death (QODD) questionnaire is used as a self-reported measure to allow families and clinicians to assess patients' quality of dying and death. We evaluated end-of-life (EOL) experiences as measured by the QODD completed by families and nurses in the United States and the Netherlands to explore similarities and differences in these experiences and identify opportunities for improving EOL care. Questionnaire data were gathered from family members of patients dying in the ICU and nurses caring for these patients. In The Netherlands, data were gathered in three teaching hospitals, and data was gathered from 12 sites participating in a randomized trial in the United States. The QODD consists of 25 items and has been validated in the United States. Data from 446 patients were analyzed (346 in the United States and 100 in the Netherlands). Dutch patients were older than those in the United States (72 + 10.2 years vs 65 + 16.0 years; P < .0025). The family-assessed overall QODD score was the same in both countries: the Netherlands = median, 9; interquartile range (IQR), 8-10 and the United States = median, 8; IQR, 5-10. US family members rated the quality of two items higher than did the Netherlands families: "time spent with loved ones" and "time spent alone." Nurse-assessed QODD ratings varied: the single-item QODD summary score was significantly higher in the Netherlands (the Netherlands: median, 9; IQR, 8-10 vs the United States: median, 7; IQR, 5-8; P < .0025), whereas the QODD total score was higher in the United States (the Netherlands: median, 6.9; IQR, 5.5-7.6 vs the United States: median, 7.1; IQR, 5.8-8.4; P = .014), although it did not meet our criteria for statistical significance. Of the 22 nurse-assessed items, 10 were significantly different between the Netherlands and the United States, with eight having higher scores in the United States and 2 having higher scores in the Netherlands. The QODD was rated similarly by family members in the United States and the Netherlands but varied when assessed by nurses. These differences may be due to organizational or cultural differences between the two countries or to expectations of respondents.